Functional foods - Csapó János; Albert Csilla; Szigeti Tamás János (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2019)
Functional foods are products that contain the ingredients in sufficient quantities, but have a greater impact on vital functions than traditional foods, contribute to the prevention of diseases, have a health protection effect, and thus overall they have a par-ticularly beneficial effect on the human body. The key question in the production of functional foods is to determine what additional component should be added to the product so that the desired functional effect, especially supportive of life process-es, can develop in the human body. Before being released for public consumption, the physiological effects of functional foods, the good manufacturing practice of the product, consumer needs, food safety related to functional foods and legal regulation should be clarified. The production of functional foods is a relatively new area where technology development and consumer acceptance are still taking place today, so producers and consumers can even co-manage processes that will be incorporated into traditional food production practices in a few years’ time. In the first half of our article, the basic concepts of functional foods are discussed, then the characteristic properties of some functional foods produced by supplement-ing foods with chemical substances are described. Due to the length limitations of the article, discussion of products manufactured with microbiological live cultures is planned for a later time.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék